Lessons from the first cohort participants’ interaction and feedback of Module 4 of the UNESWA’s short learning programme entitled Artificial Intelligence for Educations - Karen Ferreira Meyers (Sriwijaya University Learning and Education International Journal, 2025)
This paper examines participant interactions and feedback during Module 4 of the University of Eswatini's professional development course on artificial intelligence in education. The module, focused on AI case studies across different subject areas, was designed to help educators envision and implement AI integration in their specific teaching contexts. The study analyzes the responses and engagement of one pilot group of 15 participants and one cohort of 100 participants who were required to select four subject areas from fourteen options, including mathematics, modern languages, sciences and humanities and who took the 6-week course in October-November 2024. Through analysis of forum participation and activity completion, the paper explores how educators interpreted and adapted AI applications from various disciplines to their own teaching practice.  Particular attention is paid to the participants' required task of identifying five AI implementation strategies for their subject areas. The findings shed light on educators' practical grasp of integrating AI within various educational settings, highlighting their ethical concerns and innovative strategies for tailoring AI tools to suit their specific disciplinary requirements. This concise study aims to enhance our understanding of how educators from diverse subject areas perceive AI and intend to incorporate it into their teaching practices.